SOSIALISASI UNDANG-UNDANG NO. 23 TAHUN TAHUN 2011 TENTANG PENGELOLAAN ZAKAT - bambang ali kusumo; Supriyanta Supriyanta; Zulfi Rahman (Lembaga Penelitian dan Pengabdian Masyarakat, 2020)
So far, the distribution of zakat has been done by Muzaki (obliged to pay zakat, or giving zakat) giving directly to people who get zakat. The impact of this arises from queues of people who get zakat, the distribution of zakat is not evenly distributed, sometimes some get double and some don't. Therefore, it is necessary to socialize better zakat management, namely through the Amil Zakat Institution and Baznas so that the distribution of zakat can be maximally evenly distributed. The method of implementing this socialization is by giving lectures in vitual or online because it is still in a state of covid 19. From this service, community members have a better understanding and understanding of the distribution or distribution of zakat through the Amil Zakat Institute and Baznas.